The Mediating Effect of Symptoms of Anxiety on the Relationship between Appraisal and Teaching Competence - Ferrando, Gilly; Balones, Jerlyn (Yayasan Sembilan Pemuda Indonesia, 2021)
This study determined the mediating effect of symptoms of anxiety on the relationship between appraisal and teaching competence of teachers in San Isidro North and South Districts. The descriptive-correlational research design was utilized and employed stratified random sampling with 300 teachers as sample. Data collection was made through survey instruments. Data analysis was done through Mean, Pearson-r, Multiple Regression and Medgraph using Sobel z-test. Results revealed that symptoms of anxiety was high while appraisal and teaching competence were very high. A positive correlation between appraisal and teaching competence, appraisal and symptoms of anxiety, and symptoms of anxiety and teaching competence was proven in the study. The findings affirmed that symptoms of anxiety played a partial mediation thus, it cannot fully account on the influence of appraisal towards teaching competence. Moreover, a high level of symptoms of anxiety did not hinder teachers’ capability to be very highly competent in teaching.